Respostas
respondido por:
2
| 1 2 x 1 2 |
|-1 x x+1 -1 x | = 6
| 3 2 x 3 2 |
x² + 6(x+1) - 2x - [3x² + 2(x+1) - 2x] = 6
x² + 6x + 6 - 2x - [3x² + 2x + 2 - 2x ] = 6
x² + 6x + 6 - 2x - 3x² - 2x - 2 + 2x - 6 = 0
x² - 3x² + 6x - 2x - 2x + 2x + 6 - 2 - 6 = 0
-2x² + 4x - 2 = 0
================
2x² - 4x + 2 = 0
--- --- ---
2 2 2
==================
x² - 2x + 1 = 0 (equação do 2° grau)
a = 1
b = 2
c = 1
Δ = b² - 4ac
Δ = (-2)² - 4 . 1 . 1
Δ = 4 - 4
Δ = 0 (quando Δ = 0 temos apenas uma raiz)
=======================================
segunda fórmula
x = - b (+-) √Δ
2a
======================================
x = 2
2
x = 1
Solução x = 1
|-1 x x+1 -1 x | = 6
| 3 2 x 3 2 |
x² + 6(x+1) - 2x - [3x² + 2(x+1) - 2x] = 6
x² + 6x + 6 - 2x - [3x² + 2x + 2 - 2x ] = 6
x² + 6x + 6 - 2x - 3x² - 2x - 2 + 2x - 6 = 0
x² - 3x² + 6x - 2x - 2x + 2x + 6 - 2 - 6 = 0
-2x² + 4x - 2 = 0
================
2x² - 4x + 2 = 0
--- --- ---
2 2 2
==================
x² - 2x + 1 = 0 (equação do 2° grau)
a = 1
b = 2
c = 1
Δ = b² - 4ac
Δ = (-2)² - 4 . 1 . 1
Δ = 4 - 4
Δ = 0 (quando Δ = 0 temos apenas uma raiz)
=======================================
segunda fórmula
x = - b (+-) √Δ
2a
======================================
x = 2
2
x = 1
Solução x = 1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás